A Comparative Study on People With Disabilities In India: a Framework: Challenging the Discrimination Barrier: A Framework for Empowering People with Disabilities in India (Journal of Advances and Scholarly Researches in Allied Education, 2011)
There are 600 million persons with disabilities in theworld today. Eighty percent of them live in developing countries. A staggering90 million people in India are disabled. That’s almost one in every ten. Thesefigures in the very beginning of this article are not mentioned to create anysympathy for persons with disabilities. The aim of mentioning these figureshere is to illustrate that still 600 million persons with disabilities arebeing prevented from contributing to the world society (whether socially oreconomically) because of the barrier called disability. However, there has beena shift in international thinking on disability from largesse-based perspectiveto rights-based perspective. The world for and of the disabled is changing at arapid pace and the aspirations as well as expectations of people are alsochanging as fast. Advances in medical and surgical sciences, breakthroughs intechnology, greater understanding of the causes of disability and improvedmethods of coping with it, increasing consciousness of civil rights and theemergence of people with disabilities displaying skills and knowledge toimprove their own lives, are some of the factors which have contributed to thenew thinking. It is now recognized that the disabled deserve a dignified statusin society on the same terms as the non-disabled. Disabled people are a vastminority group, which has been subjected to direct and indirect discriminationfor centuries in most countries of the world, including India.